Reliability back analysis of a 3D wedge slope based on the nonlinear Barton-Bandis failure criterion. (October 2021) - Zuo, Shi; Hu, Changwen; Zhao, Lianheng; Jiao, Kangfu; Lei, Zhibin; Huang, Dongliang; Zhu, Zhiheng
Highlights: The Schmidt Hammer and photogrammetry are adopted for the initial values determination. The stability of 3D wedge slope with Barton-Bandis failure criterion was analyzed. Proposed a reliability back analysis method for nonlinear strength parameters estimate. Abstract: Due to the development of joints, wedge failure has become the main failure type of rock slopes. Obtaining accurate parameters is an important prerequisite in studying slope stability. However, these are difficult to obtain due to the restrictions of field conditions. Based on a real and simple wedge, the method of stability analysis and parameter acquisition of a wedge with the nonlinear Barton-Bandis failure criterion is discussed, and then this method is extended to the conventional form of a wedge. With minimal available data, a simple field test and the reliability back analysis method are combined to propose a specific method for determining the most likely combination of nonlinear strength parameters when wedge failure occurs. This approach can provide a simple and practical method for determining the nonlinear strength parameters for engineering applications. Thus, the small frequent collapse incidences in jointed rock slopes can be effectively utilized to provide a reference for the prevention and control of large-scale failure.